L’application des méthodes "Think-Aloud Protocol" et analyse conversationnelle à la didactique de traduction - Borowczyk, Paulina (AMU Press, 2011)
The article presents a Think Aloud Protocol study and conversation analysis implemented as strategies by inexperienced translators who translated an extract of an audiovisual message from French into German. We observed and analysed the case in which were recorded the students in order to externalize the process of translating. The author of this paper wants to show how they used different understanding and search strategies during the act of translation. The results can serve as hypotheses for the teaching of translation.
Application of Two Methods: Think-Aloud Protocol and Conversation Analysis in Teaching Translation